Delay in Construction Project Due to Movement Control Order - Raden Baharin, Raden Nuralya Afiqah; Suratkon, Azeanita (Recent Trends in Civil Engineering and Built Environment, 2021)
Malaysia is one of the countries in the world that is badly affected by the Covid-19 virus. Due to the MCO implemented by government, construction projects were instructed to stop all their works at construction site. All parties that were related with the project were likely to face damaged, especially the contractors. This research identifies the common factors related problems due to MCO and mitigation actions taken to avoid prolonging the delay. Questionnaire forms were distributed among Grade 6 contractors’ companies in Johor. The process of data analysis was conducted by using descriptive statistic that ranked the mean values. By using ranking method, confusion on SOP compliances were recognized as the most significant contribution to the delay and proper planning were recognized as the highest mitigation actions taken to avoid prolonging the delay. The common delay related problems and mitigation actions highlighted in this study will be useful for key players in the construction industry especially contractors in making necessary strategy and preparation if similar predicament happens in the future.